Sengketa Tanureal: Refleksi Pertentangan Sentralisme Hak Menguasai Negara dalam UUPA dengan Kepentingan Masyarakat Adat - Muhammad Syamsudin; Ahmad Basuki (Fakultas Hukum Universitas Islam Indonesia, 2003)
The UUPA is a transitional act product which is made to change the characteristic of colonial Law of agrarian field into the agrarian law which is in accordance with the form and idea of Indonesia Republic Unitary State. In practice, during the new order regime,the authorities abused the State Authorization Right and gave the investors the privileges of controlling the agrarian sources. As a consequence, the existency and community role of the custom were getting marginilized and felt ata disadvantage. This reality frequenthy triggered to cause the tenureal disputes between the investors and the custom community which, in general, enabled to threat the integrity of national territory/ unity. In the effort of preventing the recurrence, the UUPA needs reforming the characteristic of agrarian law which not only accomodating but also warranting the interests ofcustom community. Pluralism of agrarian law should reflect more the spirit of Unity in diversity.